THE USE OF WILSON EQUATION, NRTL AND UNIQUAC IN PREDICTING VLE OF TERNARY SYSTEMS - Yustia Wulandari, Agung Rasmito, (Jurnal Teknik Kimia, 2010)
There binary pairs of aceton-butanol, aseton-ethanol, n-butanol-ethanol and ternary pairs ofaceton-butanol-ethanol have been measured under atmospheric pressure. The equipment used forthis experimental work was the Modified Glass-Othmer Still. The analyses performed with aShimatzu gas chromatograph. Thermodynamic consistency of the observed binary VLE areconfirmed by the area test, which show that the experimental data of all of binary systems arethermodinamically consistent. The observed activity coefficients are correlated with the Wilson,NRTL dan UNIQUAC equations. The binary interaction parameters in each equation aredetermined by using the Gaussian technique, where the sum of squares of deviation in excessGibbs energy is minimized. The Wilson, NRTL dan UNIQUAC equation agree well with theexperimental data, except that the NRTL equation has second parameter different from theproposed value. The ternary VLE for aceton-butanol-ethanol system is calculated by using binaryinteraction parameter of Wilson, NRTL dan UNIQUAC obtained from three pairs binaryexperimental data. The ternary experimental data were also compared with those predicted byadopting the Wilson, NRTL dan UNIQUAC models. Based on these deviations, the Wilson modelseems to be the potential candidate to be used to predict the VLE ternary mixture for those system.Keywords : VLE, Wilson, NRTL, UNIQUAC